BACK TO THE LIGHTNESS OF LIFE: LITERARY STORIES AND (IN) TRANSCULTURALITY - Wolkoff, Gisele Giandoni; Gallian, Dante; Bittar, Yuri (Seven Editora, 2026)
We will present how narratives read in a manner detached from traditional literary criticism, within the context of humanization—particularly in the field of healthcare—constitute a proposal developed at the Humanities Laboratory (hereinafter referred to as Labhum), originating from the Center for the History and Philosophy of Health Sciences (Cehfi) of the Paulista School of Medicine (EPM) at the Federal University of São Paulo, and later extended to the Reading Laboratory (Lablei) in corporate contexts, an initiative that has opened transcultural possibilities for a broader understanding of hypermodernity. The case presented here involves the selection of two classics from literature and cinema, namely the novel The Picture of Dorian Gray (1890) by Oscar Wilde and the film Blow-Up (1967) by Michelangelo Antonioni, for discussion in one of the classes during the first semester of 2025. To this end, we start from the premise that hypermodern society and the frenetic pace of cyberspace demand an even greater awareness and heightened consciousness of our subjective and social existences and belongings. In parallel, we philosophically ground our study in the idea of transculturality—that is, different times, spaces, and ideas converging in processes of humanization such as those proposed by Labhum and Lablei. DOI: https://doi.org/10.56238/sevened2026.008-100